Maternal perinatal anxiety: A review of prevalence and correlates. (4th March 2015) - Leach, Liana S.; Poyser, Carmel; Fairweather‐Schmidt, Kate
Abstract: Background: A growing body of research has examined maternal anxiety symptoms and disorders during the perinatal period. This systematic review provides an update of the literature reporting on the prevalence and risk factors for maternal perinatal anxiety. Methods: Three databases (PubMed, PsycInfo and Web of Science) were searched to identify articles focused on the prevalence and risk factors for maternal perinatal anxiety published between 2006 and 2014. Initially, 1416 unique papers were identified, and 98 papers met the inclusion criteria for the review. Results: Maternal perinatal anxiety is common. The number of studies reporting prevalence estimates for perinatal anxiety disorders has grown; however, there is wide variation in reported estimates (2.6–39% for "any anxiety disorder"). Prominent risk factors identified included socio‐economic disadvantage, history of poor mental health, adverse circumstances around the pregnancy and birth, and poor quality partner relationships. Complexities in reviewing this literature include significant heterogeneity in study methodology. Conclusions: There is a substantial evidence‐based reporting prevalence estimates and identifying the key risk factors for maternal anxiety during the perinatal period. However, there is further need to synthesise the available literature in a meaningful way in order to translate findings into useful screening tools and intervention programs. Abstract :